2021
DOI: 10.1073/pnas.2101817118
|View full text |Cite
|
Sign up to set email alerts
|

Origin of enhanced water oxidation activity in an iridium single atom anchored on NiFe oxyhydroxide catalyst

Abstract: The efficiency of the synthesis of renewable fuels and feedstocks from electrical sources is limited, at present, by the sluggish water oxidation reaction. Single-atom catalysts (SACs) with a controllable coordination environment and exceptional atom utilization efficiency open new paradigms toward designing high-performance water oxidation catalysts. Here, using operando X-ray absorption spectroscopy measurements with calculations of spectra and electrochemical activity, we demonstrate that the origin of wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(62 citation statements)
references
References 43 publications
1
61
0
Order By: Relevance
“…45 The viability of such out-of-plane ions is nonetheless supported by the entirety of data presented here, and by recent reports for tetrahedral iron sites atop cobalt hydroxides, 34 iron oxide clusters atop nickel hydroxides, 35 and iridium ions atop nickel hydroxides. 36…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…45 The viability of such out-of-plane ions is nonetheless supported by the entirety of data presented here, and by recent reports for tetrahedral iron sites atop cobalt hydroxides, 34 iron oxide clusters atop nickel hydroxides, 35 and iridium ions atop nickel hydroxides. 36…”
Section: Resultsmentioning
confidence: 99%
“…33 Parallel studies have identified non-traditional coordination sites in nominally LDH materials, including iron ions situated outside of the 2-dimensional framework in Co(OH) 2 , 34 iron ions on terrace sites of γ-NiOOH, 35 and iridium ions anchored to the basal plane of Ni(OH) 2 . 36 Changes in behavior have also been achieved by mixing of nickel hydroxide and iron oxyhydroxide, 35 inclusion or exchange of anions between the LDH layers, 37–39 and through combination of anion exchange with immobilization of single Pt atoms. 40 The diversity of possibilities motivated us to explore variations in fabrication protocols as a means to study small changes in composition-dependent structure in an effort to identify non-traditional coordination environments in nickel-based layered double hydroxides.…”
Section: Introductionmentioning
confidence: 99%
“…In the past years, single-atom catalysts (SACs) with atomically dispersed active sites have gained great attention for high atom utilizations and unique catalytic activities. It is reported that single atoms as dopants could dramatically improve the catalytic performance. Recently, several successful attempts have been made to incorporate single atoms into spinels with enhanced electro-oxidation activity. For example, Wang et al reported selective adsorption of the CC groups in 5-hydroxymethylfurfural (HMF) by constructing single-atom-Ir-loaded Co 3 O 4 for enhanced HMF electro-oxidation (HMFOR) .…”
Section: Introductionmentioning
confidence: 99%
“…Single-atom catalysts (SACs) featuring utmost atom-utilization efficiency and tunable electronic structure can break the limitations of heterogeneous catalysts in terms of the kinetics and catalytic activity ( 20 , 21 ). Thus, SACs show a great potential to address the slow reaction kinetics of PMS for the Fenton-like process via maximizing the number of catalytic sites ( 22 ).…”
mentioning
confidence: 99%